Potensi Produksi Metana dari Limbah Kotoran Sapi dan Mitigasi Emisinya di Kabupaten Pati Jawa Tengah - Bagas Mukti Kumudasmoro; Endang Kusdiyantini; Sutaryo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study aims to quantify the biogas potential of beef cattle waste in Pati Regency, specifically the methane (CH₄) content, and to formulate mitigation measures for greenhouse gas (GHG) emissions generated from this waste. The method used is a quantitative method based on the Intergovernmental Panel on Climate Change (IPCC) approach, supported by field observations, interviews with livestock farmers from several sub-districts, and cattle population data sampling. The results indicate that the potential methane gas production in Pati Regency reaches 1,763 m³ per day, with the largest potential in Jaken District at 201 m³/day and Margoyoso District at 160 m³/day. Furthermore, greenhouse gas emissions from beef cattle waste in Pati Regency are estimated to reach 5.49 GgCO₂ eq. In conclusion, Pati Regency has great potential to utilize beef cattle waste as a renewable energy source in the form of biogas, while facing a significant threat from unaddressed methane emissions. Therefore, a SWOT analysis-based mitigation strategy is needed, including developing a pilot methane gas processing project involving collaboration between livestock breeders, academics, and local governments, as well as increasing community participation through education on the benefits of environmentally friendly waste management. Keywords: Greenhouse Gas (GHG) Emissions, Methane Gas (CH4), IPPC, Pati Regency, Beef Cattle Waste.